Pengembangan Aplikasi Mobile Manajemen Indekos berbasis Android dengan Metode Human-Centered Design (Studi Kasus: Kos Bu Parjo) - Adji Pangestu Wicaksono; Agi Putra Kharisma; Riswan Septriayadi Sianturi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Many office employees who live in Cikoko sub-district, Pancoran, stay in boarding rooms. Kos Bu Parjo is one of those that provides boarding rooms. Kos Bu Parjo still does the bookkeeping without a digital backup. The bookkeeping cannot be accessed when the notebook is not within reach, missing, exposed to water, or if a natural disaster occurs. To solve that problem, an Android application using Flutter framework and Firebase with Human-Centered Design method is developed. The main features of the app are occupant management, financial records, building management, room management, business management's account management, and backup and restore. The application went through validation testing with black box, usability testing with system usability scale, compatibility testing, and availability testing. Validation testing reveals that the application successfully fulfilled all 51 specified functional requirements, usability testing from 5 test subjects reveals the application is acceptable with an overall score of 77.75, compatibility testing reveals that the application successfully fulfilled the used Android version requirement, and availability testing reveals that the application's data recording features are operational even while offline.